Facing further challenges in cancer data quality and harmonisation - Giusti, Francesco; Martos, Carmen; Carvalho, Raquel N.; Zadnik, Vesna; Visser, Otto; Bettio, Manola; Van Eycken, Liesbet (Frontiers in Oncology, 2024)
This article highlights the recent and ongoing activities of European population-based cancer registries (PBCRs) in data quality and harmonisation in the framework of the collaboration between the European Network of Cancer Registries (ENCR) and the Directorate-General Joint Research Centre (JRC), the science and knowledge centre of the European Commission.The article concludes the Frontiers in Oncology's Research Topic "Joining Efforts to Improve Data Quality and Harmonization Among European Population-Based Cancer Registries", which has been an opportunity for several European researchers to share their experience on cancer data quality and harmonisation. Such experience will be helpful for PBCRs in view of future challenges and opportunities in cancer epidemiology, with a few examples discussed in the present article.